2013
DOI: 10.3906/sag-1206-99
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of immune responses to hepatitis A vaccination in children aged 1 and 2 years

Abstract: Th e eff ects of inoculum concentrations and the aggressiveness of spot blotch (Bipolaris sorokiniana (Sacc.) Shoemaker) isolates were evaluated on the resistance of 123 winter wheat advanced breeding lines developed from European winter wheat as well as on 3 control cultivars, BR8, BH1146, and Zentos. Th e test was conducted under laboratory conditions using a detached leaf technique. A total of 3 inoculum concentrations were used: 0.5 × 10 3 , 1 × 10 3 , and 5 × 10 3 spores mL -1 . Th e results of the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 43 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…The overall rate of local and systemic events after the first injection of the HAV vaccine was reported by Celebi et al to be 6.6-9.8% among participants who started their schedule at age 1 or 2 years. No local or systemic events were reported after the second injection in those who started vaccination at age 1 year, but were reported at a similar rate as after the first injection in those who started vaccination at age 2 years [42]. Yoon et al also reported pain as the most common adverse event in adolescents aged 13 to 19 years (32% received the pediatric HAV vaccine dose) post-dose 1 (22%; 11/51) and post-dose 2 (18%; 9/50) [49].…”
Section: Safety Profile From Pooled Clinical Studies and Literature Rmentioning
confidence: 80%
See 4 more Smart Citations
“…The overall rate of local and systemic events after the first injection of the HAV vaccine was reported by Celebi et al to be 6.6-9.8% among participants who started their schedule at age 1 or 2 years. No local or systemic events were reported after the second injection in those who started vaccination at age 1 year, but were reported at a similar rate as after the first injection in those who started vaccination at age 2 years [42]. Yoon et al also reported pain as the most common adverse event in adolescents aged 13 to 19 years (32% received the pediatric HAV vaccine dose) post-dose 1 (22%; 11/51) and post-dose 2 (18%; 9/50) [49].…”
Section: Safety Profile From Pooled Clinical Studies and Literature Rmentioning
confidence: 80%
“…The literature search identified 11 [39,40,[42][43][44][45][46][47][48][49][50] reports for inclusion in this review ( Figure S1). Although one article by Fisenka et al should have been excluded from this review because it assessed the use of three hepatitis A vaccines (i.e.…”
Section: Literature Identifiedmentioning
confidence: 99%
See 3 more Smart Citations